The Effectiveness of Interactive Multimedia 3D Modeling of Metallic Bondings to Optimize Visual-Spatial Intelligence - Irvandar Nurviandy; Kusumawati Dwiningsih (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
The research aims to test the effectiveness of three-dimensional (3D) modelling of metallic bonding as a learning media to optimize student visual-spatial intelligence. The respondents of this research were 25 students of the class 2017 in Universitas Negeri Surabaya. Data was collected online three times, including initial knowledge test, small group test, and large group test. The data collection method uses multiple-choice tests consisting of ten questions about metallic bonding and five visual-spatial questions. There is a 20-minute limit to answer all those questions after getting the experience to use the media. The effectiveness is analyzed based on classical learning completeness obtained from the average individual completeness value. Based on the results, the interactive multimedia 3D metallic bonding model effectively optimizes visual-spatial intelligence. The percentage of classical completeness in the small and large groups is 75.00 and 76.00 (%), respectively. This value is classified into the high category based on the recapitulation of student learning outcomes level.